The effect of metformin on ghrelin serum level in type 2 diabetes mellitus - Mohammed Nabel Mohammed; Nahla O M Tawfik (University of Mosul, 2013)
Objectives: Ghrelin is an orexigenic peptide hormone. A great deal of evidence suggests that ghrelin is involved in the development of type 2 diabetes mellitus (DM). The aim of this study was to investigate the effect of metformin on ghrelin serum level in type 2 DM patients. Patients and methods: This case control study was carried out in Al-Wafaa medical center for diabetic and endocrine disorder patients in Mosul from October 2011 to March 2012. In this study 55 type 2 diabetic patients and 20 control healthy subjects was participated. Those patients and subjects was divided into 4 groups. Blood samples had been collected from all subjects and patients and body mass index (BMI) had been calculated for each patient. Fasting blood sugar (FBS) level and ghrelin serum level were estimated for each patient. Results: The study shows a non significant lower mean ghrelin serum level in control diabetic group in comparison to that of control healthy group. There is significant difference in ghrelin serum level between control diabetic patients group and diabetic patients' group using metformin 1000 mg daily at P < 0.05. Ghrelin serum level has a negative correlation with ages more than 30 years old and BMI in both healthy and diabetic individuals. Conclusion: Ghrelin serum level in diabetic patients is tends to be lower when compared with healthy subjects. Metformin increase ghrelin serum level in diabetic patients and this increment was related to the dose and duration.